Addressing barriers to mental healthcare access for adolescents living in slums: A qualitative multi-stakeholder study in Odisha, India - Pallavi Behera; Jayashree Parida; Narendra Kakade; Sanghamitra Pati; Subhendu Kumar Acharya (Child. Youth Serv. Rev., 2023)
Background: The burden of mental health problems is a leading issue in India, particularly among adolescents. According to the National Mental Health survey, 2016, the prevalence of mental health problems among the age group of 13-17 years is 7.3 % and the case is the same for both genders. It has also been stated that the prevalence rate is higher among urban adolescents compared to rural ones. Adolescent mental healthcare is a neglected area in Indian society as a result it influences mental healthcare access in India. The present study, therefore, aims to provide an amalgamated overview of the adolescent mental healthcare policies and programs in India and also to find out the challenges and barriers faced by the stakeholders with respect to delivery and access to adolescent mental healthcare.Methods: To identify the challenges in the implementation of the policies, the thematic framework analysis was used to address the issues pertaining to the delivery and access to mental healthcare. The study involved the stakeholders including healthcare providers (n = 8): non-governmental organizations (NGOs), government stakeholders and adolescents (beneficiaries or service users) (n = 25) and their parents (n = 6).Results: The results indicated that there was a gap with respect to awareness and knowledge about mental health and healthcare-related access and delivery among the selected stakeholders. Stigmatization and social distance behaviors were the major prevailing factors among the adolescent participants which influenced their careseeking behavior and decision-making approach. From program and policy point of view, the key challenges affecting the successful implementation of mental health policies and programs were the lack of collaboration among the stakeholders, funding and logical constraints, scarcity of staff at the facility level, and lack of skills and knowledge among the staff.Conclusion: An integrated and multisectoral approach in adolescent mental healthcare policies and programmes is the need of the time to address the key challenges to mental healthcare access and delivery. Focused intervention is required to reduce the stigma and social distance behaviour among adolescent beneficiaries.
Keywords: Health services research; Rehabilitation; Therapeutics